Pendekatan Tafsir Modern Interpretasi Teologis, Kultural, dan Logis - Muhammad Shodiq (Institut PTIQ Jakarta, 2018)
This article questions about the modern interpretation ap- proach, namely interpretation. Among the interpretations common- ly used in the interpretation of the Koran are textual interpretations, linguistic interpretations, systematic interpretations, socio-historical interpretations, theological interpretations, cultural interpretations, and logical interpretations. All of these interpretation techniques dif- fer from interpretation methodology tools in the form of methods and approaches. Interpretation places more emphasis on the interpretation process through the method of analysis and interpretation of the data which is based on interpretation. This article also describes as much detail as possible about 3 interpretations, namely theological, cultural, and logical interpretations as a design of modern interpretations that refer to scientific research methods. This proves that, the activity of in- terpreting the Koran is an activity that is scientifically and empirically accountable like applied sciences that require scientific reasoning.